2022
DOI: 10.1039/d2tc00198e
|View full text |Cite
|
Sign up to set email alerts
|

An S-shaped double helicene showing both multi-resonance thermally activated delayed fluorescence and circularly polarized luminescence

Abstract: We present the first example of a multi-resonant thermally activated delayed fluorescent (MR-TADF) extended helicene, Hel-DiDiKTa. This S-shaped double helicene exhibits sky-blue emission, a singlet-triplet energy gap, EST, of 0.15...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 112 publications
4
36
0
Order By: Relevance
“…Furthermore, the high molecular rigidity contrib- In 2022, Zysman-Colman et al reported the ketone derivatives named Hel-DiDiKTa with an S-shaped helicene structure. [30] The extended π conjugations also obey the donor and acceptor distribution rule for MR-TADF, which lead to the slight redshifted with sky-blue narrow-band emission (λ PL = 473/478 nm, FWHM = 44/52 nm in toluene/doped film, respectively) compared with the core QAO (λ PL = 466 nm, FWHM = 32 nm in toluene). Although Hel-DiDiKTa exhibited high molecular rigidity, it does exhibit low PLQY (< 10 %) in doped 1,3-bis(Ncarbazolyl)benzene (mCP) films with various doping ratios.…”
Section: Fusing Modification By Mr Groupmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the high molecular rigidity contrib- In 2022, Zysman-Colman et al reported the ketone derivatives named Hel-DiDiKTa with an S-shaped helicene structure. [30] The extended π conjugations also obey the donor and acceptor distribution rule for MR-TADF, which lead to the slight redshifted with sky-blue narrow-band emission (λ PL = 473/478 nm, FWHM = 44/52 nm in toluene/doped film, respectively) compared with the core QAO (λ PL = 466 nm, FWHM = 32 nm in toluene). Although Hel-DiDiKTa exhibited high molecular rigidity, it does exhibit low PLQY (< 10 %) in doped 1,3-bis(Ncarbazolyl)benzene (mCP) films with various doping ratios.…”
Section: Fusing Modification By Mr Groupmentioning
confidence: 94%
“…In 2022, Zysman‐Colman et al. reported the ketone derivatives named Hel‐DiDiKTa with an S‐shaped helicene structure [30] . The extended π conjugations also obey the donor and acceptor distribution rule for MR‐TADF, which lead to the slight red‐shifted with sky‐blue narrow‐band emission ( λ PL =473/478 nm, FWHM=44/52 nm in toluene/doped film, respectively) compared with the core QAO ( λ PL =466 nm, FWHM=32 nm in toluene).…”
Section: Mr‐type Derivativesmentioning
confidence: 99%
“…Zysman‐Colman and co‐workers reported an S‐shaped double helicene, Hel‐DiDiKTa , with a CPL activity based on the helical chirality. [ 120 ] Hel‐DiDiKTa exhibited a blue‐emission peak at 473 nm with moderate FWHM PL of 44 nm in toluene. TADF behavior was observed owing to its small Δ E ST of 0.15 eV; however, the Φ PL values were extremely small both in toluene solution (Φ PL = 1.34%) and as a doped film (Φ PL = 4.1%, 1 wt% doped in mCP).…”
Section: Carbonyl/nitrogen (Co/n)‐based Mr‐tadf Materialsmentioning
confidence: 99%
“…Nevertheless, the multiple-resonance (MR) induced TADF (MR-TADF) effect with the B/N doped polycyclic fused aromatic structure provides the possibility of constructing helicene-Page 2 of 16 CCS Chemistry 3 based purely organic TADF emitters. [17][18][19][20][21][22][23][24][25] On the one hand, the complementary resonance effects of the electron-deficient B and electron-rich N/O atoms can effectively separate the frontier molecular orbitals (FMOs), which induces the short-range charge transfer to achieve a small ΔE ST for efficient TADF. [26][27][28] On the other hand, from the perspective of chemical structure, the inherent fused aromatic structures of MR-TADF effect represent a perfect platform for constructing heterohelicenes, which excludes the use of D/A units.…”
Section: Introductionmentioning
confidence: 99%